Fjenden fra Nord - Høgenhaven, Jesper (Dansk Teologisk Tidsskrift, 2016)
The years 1900-1950 were a fruitful and productive period in Old Testament research in the Nordic countries. Represented by internationally renowned figures like Johannes Pedersen, Sigmund Mowinckel, and Ivan Engnell, Scandinavian Old Testament scholarship gained an independent profile over against the German and Anglo-Saxon realms. This article explores themes of central importance to Nordic scholars in this period, and attempts to spell out some of the more significant nuances and differences among them. Finally, I raise the question to which extent we can meaningfully speak of tendencies and features common to Scandinavian Old Testament scholars 1900-1950, and whether such tendencies reflect more general cultural trends of their time. I tentatively point to some common denominators: A comparative approach that takes seriously the ancient Near Eastern context of the Old Testament texts, a marked emphasis on cultic perspectives, and an interest in the role played by orality in the formation of Old Testament literary genres and texts. Despite some very different accents put by various scholars, these points may be described as characteristic of Scandinavian scholarship in the period.